Analisa Keakuratan Kadar Glukosa Darah Menggunakan Clarke-Error Grid Analisis pada Alat Ukur Non-invasive menggunakan Sensor Photoacoustic - Usman Umar; Risnawaty Alyah; Imran Amin (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2020)
Blood glucose is a very important element in the human body, but if it is deficient or excessive, it can cause chronic disease that can lead to death. To prevent this, it is necessary to monitor cholesterol and blood glucose levels regularly, at this time the tool for measuring blood glucose levels is still an invasive method by taking a blood sample at the fingertip by injuring it. This study aims to develop a non-invasive blood glucose measuring device using a Photoacoustic Spectroscopy sensor in the range of values from a laser pulse source (λ = 650 nm) which can detect glucose signals in the blood. The method of developing this research is by designing a non-invasive measuring instrument and measuring blood glucose levels in male and female participants to create a linearity equation between blood glucose levels and the output voltage from the sensor, then mathematically obtained a polynominal equation to convert the voltage to values. blood glucose level. Validation of measuring instruments designed by comparing invasive measuring instruments as a reference, using the Clarke EGA to determine accuracy based on the classification of values of blood glucose and blood cholesterol levels based on reference. The results of the Clarke EGA analysis show that all measurement data is in Zone A so that the measuring instrument with a photoacoustic sensor can be accepted.